ON THE EXPEDIENCY OF THE SYNTHETIC POLYMER COMPOSITES USE, AIMING AT THE PLANT PROTECTION FROM THE DISEASE PATHOGENS (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
The polymers used as plant protectors have to be tested on their capacity of being destructed by soil fungi, which is due to the polymer chemical composition, as well as to the preparation ingredients.
Keywords: plant protectors; polymers; soil fungi; chemical composition